2015
DOI: 10.1123/jpah.2013-0521
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Adults’ Participation in Specific Activities: Behavioral Risk Factor Surveillance System—2011

Abstract: Background There is little information on national estimates for participation in types of aerobic activities among U.S. adults. Current estimates are important to develop appropriate and effective interventions to promote physical activity and interpret bias for some activities measured with devices. Methods The percentage of adults participating in specific aerobic activities was estimated overall and by demographic subgroups. The 2011 Behavioral Risk Factor Surveillance System respondents (N = 446,216) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 16 publications
1
49
0
Order By: Relevance
“…Young men’s relatively high levels of participation in sports and exercise decline with age, as reported for the UK [56] and the USA [57], and it is possible that men adopt walking for leisure as a replacement for more vigorous activities as they get older.…”
Section: Discussionmentioning
confidence: 99%
“…Young men’s relatively high levels of participation in sports and exercise decline with age, as reported for the UK [56] and the USA [57], and it is possible that men adopt walking for leisure as a replacement for more vigorous activities as they get older.…”
Section: Discussionmentioning
confidence: 99%
“…13 Finally, the Behavioral Risk Factor Surveillance System assesses the 2 top nonoccupational physical activities in past month; in 2011, 47% of adults reported walking as one of the two. 14 The different surveillance systems use disparate measures (bout, trip or principal commuting mode) and methods (diary or questionnaire) to assess walking, yielding estimates that are difficult to compare across systems.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A study based on the 2011 BRSS data reported that walking was the most common activity overall and among most subgroups examined. 14 Studies also have shown that greater park land density is associated with higher levels of residents who meet activity recommendations. 15 Self-efficacy also is related to independent physical activity among older adults.…”
Section: Discussionmentioning
confidence: 99%